3D virtual planning in orthognathic surgery and CAD/CAM surgical splints generation in one patient with craniofacial microsomia: a case report - Vale, Francisco (2016)
Objective: In this case report, the feasibility and precision of tridimensional (3D) virtual planning in one patient with craniofacial microsomia is tested using Nemoceph 3D-OS software (Software Nemotec SL, Madrid, Spain) to predict postoperative outcomes on hard tissue and produce CAD/CAM (Computer Aided Design/Computer Aided Manufacturing) surgical splints. Methods: The clinical protocol consists of 3D data acquisition of the craniofacial complex by cone-beam computed tomography (CBCT) and surface scanning of the plaster dental casts. The ‘‘virtual patient’’ created underwent virtual surgery and a simulation of postoperative results on hard tissues. Surgical splints were manufactured using CAD/CAM technology in order to transfer the virtual surgical plan to the operating room. Intraoperatively, both CAD/CAM and conventional surgical splints are comparable. A second set of 3D images was obtained after surgery to acquire linear measurements and compare them with measurements obtained when predicting postoperative results virtually. Results: It was found a high similarity between both types of surgical splints with equal fitting on the dental arches. The linear measurements presented some discrepancies between the actual surgical outcomes and the predicted results from the 3D virtual simulation, but caution must be taken in the analysis of these results due to several variables. Conclusions: The reported case confirms the clinical feasibility of the described computer-assisted orthognathic surgical protocol. Further progress in the development of technologies for 3D image acquisition and improvements on software programs to simulate postoperative changes on soft tissue are required.